Historical GIS Research in Canada - Fortin, Marcel; Bonnell, Jennifer (Canadian History and Environment, 2014)
Fundamentally concerned with place, and our ability to understand human relationships with environment over time, Historical Geographic Information Systems (HGIS) as a tool and a subject has direct bearing for the study of contemporary environmental issues and realities. To date, HGIS projects in Canada are few and publications that discuss these projects directly even fewer. This book brings together case studies of HGIS projects in historical geography, social and cultural history, and environmental history from Canada's diverse regions. Projects include religion and ethnicity, migration, indigenous land practices, rebuilding a nineteenth-century neighborhood, and working with Google Earth. With contributions by: Colleen Beard Stephen Bocking Jennifer Bonnell Jim Clifford Joanna Dean François Dufaux Patrick A. Dunae Marcel Fortin Jason Gilliland William M. Glen Megan Harvey Matthew G. Hatvany Sally Hermansen Andrew Hinson Don Lafreniere John S. Lutz Joshua D. MacFadyen Daniel Macfarlane Jennifer Marvin Cameron Metcalf Byron Moldofsky Sherry Olson Jon Pasher Daniel Rueck R. W. Sandwell Henry Yu Barbara Znamirowski